The Rhetorical Use of Numbers in the Deuteronomistic History : "Saul Has Killed His Thousands, David His Tens of Thousands" - C., Flanders, Denise (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2022., 2022)
The Deuteronomistic History contains many vast troop and casualty numbers. What purpose does this literary device of numerical hyperbole serve? What rhetorical purposes do any of the numbers in this text serve? In The Rhetorical Use of Numbers in the Deuteronomistic History: "Saul Has Killed His Thousands, David His Tens of Thousands," Denise Flanders explores the variety of rhetorical effects that numbers have on the narrative of Joshua-2 Kings. Flanders demonstrates that numbers in Joshua-2 Kings often work in surprising and subversive ways. Rather than regularly glorifying a leader, large casualty numbers may actually anticipate a ruler's downfall. Rather than underscoring an Israelite battle victory, numbers sometimes qualify or undermine the triumph of victories.